Sweet Memories or Not? A Comparative Study on Cognitive Impairment in Diabetes Mellitus - Varghese, Sangeetha Merrin; Joy, Niva; John, Anulekha Mary; George, Geomcy; Chandy, George Mateethra; Benjamin, Anoop Ivan (Frontiers in Public Health, 2022)
Introduction Type 2 Diabetes Mellitus is a modern-day epidemic and dementia has been declared as a global challenge. It is, therefore, worthwhile to investigate the effect that Diabetes has on cognition. Although effective screening is routinely carried out for various complications of Diabetes, its effect on Higher Mental Functions is often overlooked. Methodology A cross-sectional analytical study to assess Cognitive Impairment was carried out on 800 participants, 400 diabetics and 400 non-diabetics attending a tertiary care center. The Addenbrooke's Cognitive Examination- III was used, which is a validated, highly sensitive tool having a maximum score of 100. Patients with a score < /= 82 were considered to have impaired Cognition. Statistical analysis was done using SPSSv.21. Suitable statistical tests like Mann–Whitney U, t-test, ROC curve and Logistic regression analysis were done. Results Cognitive Impairment was present in 63.8% of the diabetics when compared to only 10.8% in the non-diabetics, with an Odds Ratio-8.78 (CI-4.47–17.22). The total ACE score in diabetics [median-82 (IQR-4), mean rank-270.06] was less compared to the non-diabetic patients [median- 85 (IQR-3), mean rank-530.94] (U = 27822, p-0.001). Attention, Memory, Language, and Visuospatial domains were significantly lower in the diabetics compared to the non-diabetics. However, the fluency domain was not affected. Hypertension and the presence of macrovascular diseases were significantly associated with Cognitive Impairment (p < 0.005). Those with Cognitive dysfunction also had higher mean RBS values and longer duration of Diabetes (p-0.001). The cut-off value for RBS (to distinguish people with and without Cognitive Impairment) from ROC curve was 142.5 (AUC = 0.834, Youden's Index-0.586, p-0.001) and for duration of Diabetes was 7.5 years (AUC = 0.847, Youden's Index-0.529, p-0.001). Conclusion This paper highlights that Cognitive Impairment exists in a very high proportion of diabetic patients in Kerala. So, it is important that we do an early assessment of cognitive function in diabetes patients and manage them prudently. Early interventions may prove to be beneficial in the long run, considering the burden of diabetes and cognitive dysfunction associated with the disease.